Turismo agroecológico como emprendimiento sostenible desde los territorios rurales - Fernández, Alfonso José (Cooperativismo & Desarrollo, 2024)
The agricultural-livestock heritage, agro-friendly practices, climate change and the sustainability of rural territories have been the main elements for the development of agroecological tourism. This article aims to examine agroecological tourism as a sustainable enterprise from rural territories. The descriptive qualitative approach was supported through a bibliographic review of the different elements or activities that converge in the various types of tourism, based on research or scientific or indexed articles from the year 2016-2023, through the ordering of analysis matrices or heuristic phase. As a finding, 8 investigations related to the main categories were addressed, yielding 4 emerging categories (Demand, Supply, Resources and Products) of agroecological tourism, then in table 4, 13 investigations were examined (1 national; 9 international and 3 local), then they are hosted in databases, scientific journals, repositories and indexed journals, of which 11 met the criteria of the categories to be studied. As conclusions, the agroecological tourism venture promotes the incorporation of social actors, the community and service providers, taking advantage of the production units, attractions, infrastructure and services for the enhancement of agro-friendly practices and local bioculture. From there, the dissemination of the new conception of agroecological tourism from a sustainable and sustainable vision.
Keywords: Tourism; Agroecology; entrepreneurship; sustainability; rural territories